A Case Based Account Of Bantu Iav-Focus - Selvanathan, Naga (My University, 2019)
Right dislocation (Cheng & Downing 2012) and movement to a low FocP (van der Wal 2006) are competing analyses of Immediately-After-Verb (IAV) focus. In this paper, I discuss novel Lubukusu IAV focus data which shows that 1) IAV focus requires movement to a low FP and that 2) IAV focus is not a purely focus related phenomenon. Adopting Baker & Collins (2006) analysis of Linkers, I propose that movement to a low FP for focus interpretation is a strategy of case assignment to DPs within the VP. This analysis is shown to be superior to a purely right dislocation analysis as it can also better account for IAV focus asymmetries between Zulu and Lubukusu.
Keywords: Bantu; IAV-focus; Lubukusu; focus data